Pediatric and Adult Liver Disease in Alpha-1 Antitrypsin Deficiency - Ruiz, Mathias; Lacaille, Florence; Schrader, Christina; Pons, Monica; Socha, Piotr; Krag, Aleksander; Sturm, Ekkehard; Bouchecareilh, Marion; Strnad, Pavel (Seminars in Liver Disease, 2023)
Alpha-1 antitrypsin deficiency (AATD) arises due to inherited variants in SERPINA1, the AAT gene that impairs the production or secretion of this hepatocellular protein and leads to a gain-of-function liver proteotoxicity. Homozygous Pi*Z pathogenic variant (Pi*ZZ genotype) is the leading cause of severe AATD. It manifests in 2 to 10% of carriers as neonatal cholestasis and 20 to 35% of adults as significant liver fibrosis. Both children and adults may develop an end-stage liver disease requiring liver transplantation. Heterozygous Pi*Z pathogenic variant (Pi*MZ genotype) constitutes an established disease modifier. Our review summarizes the natural history and management of subjects with both pediatric and adult AATD-associated liver disease. Current findings from a phase 2 clinical trial indicate that RNA silencing may constitute a viable therapeutic approach for adult AATD. In conclusion, AATD is an increasingly appreciated pediatric and adult liver disorder that is becoming an attractive target for modern pharmacologic strategies.
Keywords: cirrhosis; hepatitis; children